First person - Callum Rakhit and Ricky Trigg (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Callum Rakhit and Ricky Trigg are co-first authors on 'Early detection of pre-malignant lesions in a KRASG12D-driven mouse lung cancer model by monitoring circulating free DNA', published in DMM. Callum is a Clinical Scientist (Bioinformatics) in the lab of Barnaby Clark at Rayne Institute, King's College Hospital, London, UK. His main research interest is identifying predictive factors in large biological datasets using informatic tools. Ricky is a Postdoctoral Research Associate in the lab of Dr Suzanne Turner at the University of Cambridge, Cambridge, UK, investigating mechanisms of resistance to targeted therapies in neuroblastoma.